2013
DOI: 10.1007/s11746-013-2354-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Vegetable Oil or Biodiesel Added to Diesel Using Fluorescence Spectroscopy and Principal Component Analysis

Abstract: In order to identify possible adulteration of onroad diesel with vegetable oil, fluorescence spectroscopy was used as the analytical technique to differentiate between vegetable oil and biodiesel in diesel blends. Diesel/oil and diesel/biodiesel blends made with different proportions of soy, canola or waste cooking oil were analyzed. The reduced cost of analysis using fluorescence spectroscopy together with the reliability of the results suggest that this technique could be of great use in differentiating betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…The concentration of biodiesel in blended fuels has been measured using various spectroscopic techniques, including infrared [3,4,5,6,7] and fluorescence [8,9] spectroscopy combined with multivariate analysis methods, such as Hierarchical Cluster Analysis (HCA), Principal Component Analysis (PCA), or Partial Least Squares (PLS). Electrospray ionization mass spectrometry has been combined with chemometric methods to analyze different feedstocks and blend compositions of biodiesel [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of biodiesel in blended fuels has been measured using various spectroscopic techniques, including infrared [3,4,5,6,7] and fluorescence [8,9] spectroscopy combined with multivariate analysis methods, such as Hierarchical Cluster Analysis (HCA), Principal Component Analysis (PCA), or Partial Least Squares (PLS). Electrospray ionization mass spectrometry has been combined with chemometric methods to analyze different feedstocks and blend compositions of biodiesel [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…7,8,[18][19][20] This way, chlorophyll contributes to biodiesel fluorescence between 665 and 675 nm. 12 Magalhães et al 20 detected the presence of chlorophyll in soybean biodiesel when the sample was excited at 532 nm.…”
Section: Resultsmentioning
confidence: 99%
“…11 These authors have also identified the adulteration of biodiesel with vegetable oil using fluorescence spectroscopy. [10][11][12] Biodiesel is chemically defined as a mixture of mono-alkyl esters of long-chain fatty acids (C16-C18) derived from vegetable oils and animal fats. It is a domestic renewable fuel for diesel engines and meets the standards and specifications provided by the American Society for Testing and Materials (ASTM D 6751).…”
Section: Introductionmentioning
confidence: 99%
“…7) Fazem a identificação de adulteração de biocombustível por adição de óleo residual ao diesel por espectrofluorimetria total 3D e análise das componentes principais 3 . 8) Determinam a adulteração de óleo vegetal por monitoramento da presença da clorofila 76,77 . 9) Determinam a estabilidade oxidativa de óleos e de biodiesel por espectrofluorimetria associada a quimiometria 5 .…”
Section: Descrição Do Métodounclassified